2012
DOI: 10.1093/humrep/des134
|View full text |Cite
|
Sign up to set email alerts
|

Expression of leukaemia inhibitory factor and interleukin 15 in endometrium of women with recurrent implantation failure after IVF; correlation with the number of endometrial natural killer cells

Abstract: The results show an altered expression of LIF and IL-15 in the endometrium of women with RIF. Despite the limitation of not identifying uNK cells by phenotypic markers, the correlation between the uNK cell number and the stromal cell IL-15 suggests that IL-15 may play a role in the control of endometrial uNK cell function or proliferation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 32 publications
1
63
0
5
Order By: Relevance
“…In agreement with these findings, another recently published study demonstrated a correlation between stromal IL15 and the number of uNK cells. However, in disagreement with these studies, it has been reported that women with repeated implantation failure have higher IL15 in the stroma compared with controls (Mariee et al 2012). …”
Section: Local Injury-induced Increase In Endometrial Receptivity Is mentioning
confidence: 86%
“…In agreement with these findings, another recently published study demonstrated a correlation between stromal IL15 and the number of uNK cells. However, in disagreement with these studies, it has been reported that women with repeated implantation failure have higher IL15 in the stroma compared with controls (Mariee et al 2012). …”
Section: Local Injury-induced Increase In Endometrial Receptivity Is mentioning
confidence: 86%
“…This association has suggested regulation by progesterone, but uNK cells do not express progesterone receptor or oestrogen receptor (ER)α Henderson et al 2003 ). Regulation of uNK cells by progesterone could occur indirectly via products of decidualised endometrial stromal cells; endometrial stromal cells produce interleukin (IL)-15 in the late secretory phase of the cycle and early pregnancy, and immunostaining for IL-15 has been shown to correlate with numbers of CD56+ cells in endometrium from women with recurrent miscarriage and implantation failure (Mariee et al 2012 ). uNK cells do, however, express ERβ and glucocorticoid receptor (Henderson et al 2003 ).…”
Section: Distribution Of Unk Cellsmentioning
confidence: 99%
“…Although IL-2 is not present in normal endometrium, IL-15 has been detected in stromal cells in luteal phase endometrium and early pregnancy decidua; secretion is stimulated by progesterone, although the regulation of this appears complex (Okada et al 2000 ), involving IL-1-β (Okada et al 2004 ) and IFNγ ( Dunn et al 2002 ). Studies of luteal phase endometrium in women with recurrent reproductive failure have shown a correlation between uNK cell number and stromal cell IL-15 levels (Mariee et al 2012 ). Although no data are available for human uNK cells, IL-11 is required for mouse uNK cell maturation (Ain et al 2004 ).…”
Section: Regulation Of Unk Cells By Growth Factors In Endometriummentioning
confidence: 99%
“…These 2 elements complement each other, promoting recovery of endometrium. As known, HOXA10 was a marker of endometrial receptivity [20,21]. An expression of sufficient HOXA10 mRNA is essential to endometrial receptivity and embryo implantation [22].…”
Section: Discussionmentioning
confidence: 96%